ANALISIS KETIMPANGAN PEMBANGUNAN ANTAR WILAYAH KABUPATEN/KOTA DI PROVINSI SUMATERA BARAT - Nurul Rifqah (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2017)
This research aims to identify and analyze the effect of (1) the labor force to imbalance regional development of West Sumatra (2) quality of human resource to imbalance regional development of West Sumatra(3) allocation of Public Funds to imbalance regional development of West Sumatra (4) government expenditure to imbalance regional development of West Sumatra. Using panel data analysis, the results of this research showed that the labor force and government expenditure has not siginificant effect to imbalance regional development of distirct/city in West Sumatra, the quality of human resource and allocation of Public Funds has significant effect to imbalance regional development of distirct/city in West Sumatra, and simultaneously there are significant effect between the labor force, quality of human resource, Allocation of public fund, and Government expenditurehas significant effect to imbalance regional development of distirct/city in West Sumatra in research period.